Tinjauan Yuridis Tentang Proses Penyelesaian Perkara Perceraian : Studi Kasus Putusan Pengadilan Agama Lubuk Pakam Nomor : 1255/Pdt.G/2023/PA.Lpk - Pajar Ningrum; Anwar Sadat (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Marriage or Marriage is a very strong contract (misaqon ghalidzan) to justify a sexual relationship between a man and a woman for the sake of realizing a happy family life, which is filled with a sense of peace and affection according to the rules approved by Allah. In legal research, there are two types of research, namely normative (doctrinal) research and empirical research. The type of research used in preparing this thesis is a combination of normative (doctrinal) research and empirical research. The location for data collection in this research was at the Lubuk Pakam Religious Court, Jalan Mahoni No.3 Komp. Deli Serdang Regency Government Offices. The technique of designating a word that is abstract and not manifested in objects, but its use can only be seen through: questionnaires, interviews, observations, exams (tests), documentation, etc. The data analysis technique used in this legal research uses qualitative analysis Based on research results, the factors that cause divorce fall into various categories such as adultery, drunkenness, madness, gambling, leaving one of the parties, prison law, polygamy, domestic violence (KDRT), constant disputes and quarrels, apostasy, and economic problems. In resolving divorce case Number 1255/Pdt.G/2023/PA.Lpk at the Lubuk Pakam Religious Court, the Panel of Judges put forward in-depth legal considerations in deciding the divorce case between Kiki Andriani Binti Giarno (Plaintiff) and Juliandi Nasution Bin Sabran Nasution (Defendant) . The following is a comprehensive explanation of the considerations made by the Panel of Judges in the decision-making process: Based on the process of resolving divorce cases, this shows how the legal system functions to handle domestic disputes by considering various legal factors and relevant facts. So it can be concluded that the factors causing divorce at the Lubuk Pakam Religious Court. In this research, an analysis of the divorce case decision at the Lubuk Pakam Religious Court with Number 1255/Pdt.G/2023/PA.Lpk between Kiki Andriani Binti Giarno as the Plaintiff and Juliandi Nasution Bin Sabran Nasution as Defendant. Based on this decision, there are several main factors that led to the divorce, which reflect the dynamics of the couple's domestic life and are relevant in the general context of divorce at the Lubuk Pakam Religious Court. Considerations of the Panel of Judges in Settlement of Divorce Cases at the Lubuk Pakam Religious Court. The decision emphasizes the importance of being present in the legal process and the effectiveness of mediation as an effort to resolve disputes. About the process of resolving divorce cases (Religious Court Decision Case Study Number: 1255/Pdt.G/2023) settlement process This divorce case shows how the legal system functions to handle domestic disputes by considering various legal factors and relevant facts.